Sutureless retropupillary iris claw intraocular lens implantation is a viable option in aphakic patients - Gohil, Neepa R.; Yadav, Sandeep Kumar; Shinde, Kaumudi (International Journal Of Community Medicine And Public Health, 2019)
Visual rehabilitation in aphakia has been a challenge with a wide variety of surgical options available for ophthalmologist. We report the visual outcome with retropupillary iris claw lens secondary to intra operative complications and secondary implantation in aphakia. An interventional study on 4 eyes of 4 patients was conducted. Preoperative visual acuity, slit lamp examination and fundus examination were carried out. Anterior vitrectomy and retropupillary fixation of iris claw lens were done. The primary outcome measure was best-corrected visual acuity and secondary postoperative complication was recorded at various intervals. All patients had visual acuity of ≥6/18 postoperatively. Sutureless retropupillary iris claw intraocular lens implantation is a good alternative of scleral-fixated intraocular lenses in aphakic patients.